Bone quality of broilers fed diets with phytase and reduced nonphytate phosphorus levels - DOI: 10.4025/actascianimsci.v30i3.496 - Oliveira, Maria Cristina de (2008)
It was evaluated the mineral content, density, weight, morphometry and breaking strength of tibiae in broilers fed diets containing phytase and reduced nonphytate phosphorus levels (NPP). The experimental design was completely randomized and factorial arrangement 2 x 3 with two phytase levels (0 and 25U/kg) and three NPP levels (100, 85 and 70% of the requirements) in a total of six treatments and five replicates. There was no effect of NNP levels and/or phytase on phosphorus and ashes levels, weight, length and diameter. Interaction NPP x phytase was significant to Ca content that was lower in tibiae of birds fed diets with 70% of NPP and with no phytase. Proximal epiphysis density decresead due the reduction of NPP and increased with phytase inclution in the diet. There was effect of the interaction NPP x phytase to diaphysis, distal epiphysis and mean densities. Breaking force decreasead in birds fed diets with 70% of NPP. Diets with 85% of NPP requirements, supplemented with 25U/kg of phytase, can be used with no negative effects on mineral content, density, weight, morphometry and breaking strength of broilers tibiae. Key words: bone density, bone mineralization, breaking strength